2016
DOI: 10.1007/s00429-016-1322-x
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine self-administration modulates glutamate neurophysiology

Abstract: World-wide methamphetamine (meth) use is increasing at a rapid rate; therefore, it has become increasingly important to understand the synaptic changes and neural mechanisms affected by drug exposure. In rodents, 6-hr access to contingent meth results in an escalation of drug intake and impaired cognitive sequelae typically associated with changes within the corticostriatal circuitry. There is a dearth of knowledge regarding the underlying physiological changes within this circuit following meth self-administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 34 publications
5
28
1
Order By: Relevance
“…In addition, such exposure is sufficient to increase the expression/ function of mGlu1/5 glutamate receptors and their associated scaffolding protein Homer2 within this region (8). Indeed, a survey of the extant literature on animal models of MA abuse supports a correlative link between potentiated indices of glutamate signaling and addiction-related behavior, including self-administration, MA-induced reinstatement of drug-seeking after abstinence or extinction, incubation of MA-craving, and conditioned place-preference (CPP) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such exposure is sufficient to increase the expression/ function of mGlu1/5 glutamate receptors and their associated scaffolding protein Homer2 within this region (8). Indeed, a survey of the extant literature on animal models of MA abuse supports a correlative link between potentiated indices of glutamate signaling and addiction-related behavior, including self-administration, MA-induced reinstatement of drug-seeking after abstinence or extinction, incubation of MA-craving, and conditioned place-preference (CPP) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have shown that long-access METH self-administration (SA; 6 h/d) increases the proportion of burst firing pyramidal cells compared to tonic firing cells in mPFC (Parsegian et al, 2011); however, it was unknown whether this increased burst firing results from presynaptic and/or postsynaptic changes. In a recent study, we found that long-access METH SA decreases AMPA/NMDA ratio in pyramidal neurons of the mPFC, accompanied by an increase in NMDA currents and surface expression of the GluN2B subunit of the NMDA receptor (NMDAR; Mishra et al, 2017). Together, these results show that METH elicits multiple forms of long-term synaptic changes in the PFC, suggesting that altered synaptic function is one of the fundamental mechanisms affected by this drug.…”
Section: Introductionmentioning
confidence: 99%
“…These data are consistent with previous reports suggesting that the expression of NMDA receptor was regulated after MA exposure and modulated the excitotoxic effect ( Bowyer and Ali, 2006 ; Kalivas and Volkow, 2011 ). Another study also reported that MA self-administration increased the NMDA receptor currents and surface expression of the GluN2B subunit ( Mishra et al ., 2017 ). In addition, the expression of GluN2B by MA is considered one of the fundamental mechanisms affected by addictive drugs ( Galinato et al ., 2015 ; Mishra et al ., 2017 ).…”
Section: Discussionmentioning
confidence: 87%
“…Another study also reported that MA self-administration increased the NMDA receptor currents and surface expression of the GluN2B subunit ( Mishra et al ., 2017 ). In addition, the expression of GluN2B by MA is considered one of the fundamental mechanisms affected by addictive drugs ( Galinato et al ., 2015 ; Mishra et al ., 2017 ). These studies suggest that the overexpression of GluN2B is an important factor in MA intoxication.…”
Section: Discussionmentioning
confidence: 87%